The Success of the Global Business Leader: The Expatriate Perspective in Ghana - Tuffour, Joseph Kwadwo; Matey, Ebenezer (Journal of Applied Business and Economics, 2019)
In a fast-changing environment, both local and international companies have found that, one of the principal problems involve the failure to effectively manage people issues. The study examines the competencies that make a successful global leader from the expatriates’ perspective in the nongovernmental organizations’ sector of Ghana. Questionnaires were administered to 300 expatriates and Ghanaians who have worked abroad. Data from the survey were analysed using correlation and regression techniques. The results of the study indicate a statistical significant effect of each of managers’ ability to appreciate cultural diversity, use of appropriate technology and proper decision-making on the success of global leaders’ performance. The study revealed that, while age of the expatriates does not make any difference in determining success, the level of education and experience do have significant correlations with the success rate of expatriates’ performance. It is therefore recommended that, organizations should aim at developing policies which embrace competences such as appreciating cultural diversity and using appropriate technology for decision-making in global organizations.